Relationship Between Hospital Image With Patient Loyalty In Hospitalized Patients - Thalia Elita Gunawan; Putri Permatasari; Marina Ery Setiawati; Dyah Utari (Jurnal Kesehatan Prima, 2020)
This research was conducted at Hospital X from May to June 2019, which aims to determine the relationship between hospital image and patient loyalty with the hospital image variables studied were Corporate Identity, Physical Environment, Contact Personnel, and Service Offering. This research uses a quantitative analytic research design with a cross-sectional approach. The population in this study was inpatients at Hospital X in May 2019. The sample in this study was 99 respondents, and the sampling technique was purposive sampling. For data analysis, this study uses the chi-square test. The results of this study are there is a relationship between Corporate Identity (company identity) with patient loyalty (p = 0.008), Contact Personnel (service provider) with patient loyalty (p = 0.019), and Service Offering (services provided) with patient loyalty ( p = 0.005). There was no relationship between Physical Environment (patient's physical environment) and patient loyalty (p = 0.710).